Machine Learning-Based Surgical Planning for Neurosurgery: Artificial Intelligent Approaches to the Cranium - Dundar, Tolga Turan; Yurtsever, Ismail; Pehlivanoglu, Meltem Kurt; Yildiz, Ugur; Eker, Aysegul; Demir, Mehmet Ali; Mutluer, Ahmet Serdar; Tektaş, Recep; Kazan, Mevlude Sila; Kitis, Serkan; Gokoglu, Abdulkerim; Dogan, Ihsan; et al. (Frontiers in Surgery, 2022)
OBJECTIVES Artificial intelligence(AI) applications in neurosurgery have an increasing momentum as well as the growing number of implementations in the medical literature. In recent years, AI research define a link from neuroscience to AI. It is a connection between knowing and understanding the brain and how to simulate the brain. The machine learning algorithms, as a subset of AI, are able to learn with experiences, perform big data analysis and fulfill human-like tasks. Intracranial surgical approaches that have been defined, disciplined, and developed in the last century have become more effective with technological developments. We aimed to define individual-safe, intracranial approaches by introducing functional anatomical structures and pathological areas to artificial intelligence. METHODS Preoperative MR images of patients with deeply located brain tumors were used for planning. Intracranial arteries, veins, and neural tracts are listed and numbered. Voxel values of these selected regions in cranial MR sequences were extracted and labeled. Tumor tissue was segmented as the target. Q Learning algorithm which is a model-free Reinforcement Learning algorithm was run on labeled voxel values (on optimal paths extracted from the new heuristic-based path planning algorithm), then the algorithm was assigned to list the cortico-tumoral pathways that aim to remove the maximum tumor tissue and in the meantime that functional anatomical tissues will be least affected. RESULTS The most suitable cranial entry areas were found with the artificial intelligence algorithm. Cortico-tumoral pathways were revealed using Q learning from these optimal points. CONCLUSIONS AI will make a significant contribution to the positive outcomes as its use in both preoperative surgical planning and intraoperative technique equipment assisted neurosurgery, its use increased.